UPAYA MENINGKATKAN MOTIVASI BELAJAR SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY - Widarti Widarti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2018)
This study aims to know the implementation, by Algebra Block in improving to understand the student’s learning success. This study was classroom action research conducted for thirthy one students in class VIII C of SMP Negeri 1 Srandakan. It had been conducted from November to Desember 2016. The data were collected using an observation sheet and questionnaires. The analysis technique of the data used quantitative descriptive method by counting the average mean of the score from the students. The results of this study are the understanding and reaction students’ learning in VIII C Class on mathematics using of Two Stay Two Stray so they get improvement. The average of students’ reaction score on the first meeting got the average 73%, the first clycle on the second meeting was 76%, the second cycle on the first meeting was 79%, and the second cycle on the second meeting got the average 82% so there was improvement 9% .All the item indicators the success which are not less than 75%, those are diligence, toughness, enthusiasm, boring, hardwork and self convidence